Hand sanitizers: is over usage harmful ? (World Journal of Current Medical and Pharmaceutical Research, 2020)
Sanitizers are the substances or the fluid designated to kill germs on skin and objects. As hand hygiene plays an important role in pandemic situations like COVID-19, people mostly rely on hand sanitizers than soap and water. The sanitizing effect of sanitizer depends on the ingredients such as 60-95% v/v alcohol, antiseptics, etc. The alcohol usually damages the skin by denaturation of stratum corneum proteins. The repeated or frequent use of hand sanitizers can cause skin reactions- Irritant contact dermatitis and Allergic contact dermatitis with symptoms such as burning, irritation, itching, etc. These effects can be reduced by using selected less irritating products, reducing skin irritation, use of moisturizing skin products. As microbial flora also plays an important role in human health, sanitizer overuse creates an imbalance between the good and bad bacteria in the digestive system which leads to inflammatory bowel diseases, obesity, autism, etc. As a researcher reported that sanitizer also gives an unpleasant side effect of using hand sanitizer every day and also mentioned that ‘we have to balance the benefit of sanitizer for preventing disease transmission and their potential misuse remains a challenge’.